Impact of adjunctive tolvaptan on sympathetic activity in acute heart failure with preserved ejection fraction - Shunsuke Tamaki; Takahisa Yamada; Takashi Morita; Yoshio Furukawa; Masato Kawasaki; Atsushi Kikuchi; Tsutomu Kawai; Masahiro Seo; Makoto Abe; Jun Nakamura; Kyoko Yamamoto; Kiyomi Kayama; et al. (ESC Heart Failure)
Abstract Aims Acute decompensated heart failure (ADHF) is generally treated by decongestion using diuretic therapy. However, the use of loop diuretics is associated with increased cardiac sympathetic nerve activity (CSNA). We aimed to evaluate the effect of adjunctive tolvaptan therapy on CSNA in ADHF patients with preserved left ventricular ejection fraction (LVEF). Methods and results We enrolled 51 consecutive ADHF patients with LVEF ≥45%. Patients were randomly assigned to receive either tolvaptan add‐on (n = 25) or conventional diuretic therapy (n = 26). Cardiac iodine‐123 metaiodobenzylguanidine (MIBG) imaging was performed after stabilisation of heart failure symptoms, and the cardiac MIBG heart‐to‐mediastinum ratio (HMR) and washout rate (WR) were calculated. There were no significant differences in the body weight change and total urine volume during 2 days after randomisation or in the HMR on delayed image (HMR(d)) and WR between the tolvaptan and conventional groups. After stratification based on the median change in body weight, the patients with higher weight reduction had a significantly lower HMR(d) (P = 0.0128) and tended to have a higher WR (P = 0.0786) in the conventional group, whereas the cardiac MIBG imaging results were not influenced by body weight reduction in the tolvaptan group. Conclusions Adjunctive tolvaptan therapy may provide rapid decongestion without a harmful effect on CSNA in ADHF patients with preserved LVEF.